The Role of Educators in Instilling Local Wisdom Values Nosarara Nosabatutu and Realizing Moderate Attitude to Madrasah Students - M Nur, Mohammad Djamil; M. Sugeng Sholehuddin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study aims to examine the role of educators in instilling the values of local wisdom Nosarara Nosabatutu to form students who have an attitude of religious moderation in the Madrasah. This local wisdom includes cultural values and local traditions that underlie the norms of life of the Nosarara Nosabatutu people. Therefore, the implementation in Madrasah in the form of character education is an effort to help students recognize, realize, and live the values of brotherhood, kinship, unity, and unity as a source of glue for social integration in the Kaili ethnic community, which can be used as a reference in behaving and behaving for Students who have an attitude of religious moderation. This research uses the Library Research method, where literature study is an activity to collect and sort out materials related to research derived from books and scientific journals. The results of the study found that Moderation in Islam is a balance that can be seen in the ability to synergize the dimensions of spirituality with materiality, individuality with collectivity, textual with contextual, consistency with change, and placing charity in the principles of balance between theocentric and anthropocentric. The local wisdom of Nosarara Nosabatutu in the local history of the Kaili tribe in the province of Central Sulawesi has a content of human values that emphasizes aspects of the value of brotherhood, kinship, unity, and togetherness as a source of glue for social integration in the Kaili ethnic community. The impact of innovation in learning is that it can enhance character values and foster love for the local wisdom of the nation.